2021
DOI: 10.1007/s12020-021-02784-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of malignancy in pediatric patients with thyroid nodules and performance of the Italian classification (SIAPEC 2014) in the outcome of the cytological FNA categories

Abstract: Purpose The rate of malignancy (ROM) among pediatric studies using the Bethesda System is 39.5% and 41.5% for atypia of undetermined significance/follicular lesion of undetermined significance and for suspected follicular neoplasm, respectively. Data reported on the basis of Bethesda System showed lower ROM in adults with indeterminate nodules (30.5 and 28.9% respectively). Studies on adults based on the Italian Society of Anatomic Pathology and Cytology (SIAPEC) classification, report ROM of 14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Other features include intranodal calcification or vascularization, lymph node involvement, marked hypoechoic pattern, bilateral or right lobe localization of the nodule, poorly defined nodule margins and some clinical risk factors, particularly radiation exposure for cancer treatment, increased TSH values, young age and male gender. In our cohort, TSH levels were correlated to malignancy, as previously reported ( 6 , 26 ). Considering the child’s body size and the presence of microcarcinomas, in presence of multiple risk factors FNAB should be performed even if the nodule size is smaller than 1 cm ( 1 7 ).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Other features include intranodal calcification or vascularization, lymph node involvement, marked hypoechoic pattern, bilateral or right lobe localization of the nodule, poorly defined nodule margins and some clinical risk factors, particularly radiation exposure for cancer treatment, increased TSH values, young age and male gender. In our cohort, TSH levels were correlated to malignancy, as previously reported ( 6 , 26 ). Considering the child’s body size and the presence of microcarcinomas, in presence of multiple risk factors FNAB should be performed even if the nodule size is smaller than 1 cm ( 1 7 ).…”
Section: Discussionsupporting
confidence: 68%
“…The cytological category assignment leads to different clinical management that includes clinical-radiological follow-up or surgery, with some differences between these classifications. Despite the differences, all agree on a higher ROM in paediatric age for all categories, especially for indeterminate nodules ( 6 , 33 , 34 ).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Pediatric thyroid diseases of surgical interest are rare: however, data provided by literature report constantly increasing incidence rates (14, 15). Children and adolescents show diseases with a worse prognosis and higher malignancy rates (12.5-50%), much higher than the adult population by 5-10% (16).…”
Section: Discussionmentioning
confidence: 99%
“…Another pediatric study cited a 50% benignity rate of AUS/FLUS lesions, calling into question the 2015 ATA recommendations for surgical resection for all these lesions [39]. A 200-patient pediatric Italian study which used its own, more nuanced, FNA reporting system, reported a total FNAB accuracy of 95% with a sensitivity and specificity of 92.3% and 92.6%, respectively [57]. A recent study examined the use of machine learning to better determine which pediatric thyroid nodules warrant FNA and surgical intervention, with the intent to avoid surgery for benign lesions [58].…”
Section: Fine Needle Aspirationmentioning
confidence: 99%